VALLESAURUS CENENSIS WILD, 1991, A DREPANOSAURID (REPTILIA DIAPSIDA) FROM THE LATE TRIASSIC OF NORTHERN ITALY (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2006)
Vallesaurus cenensis, a small drepanosaurid reptile from the Norian (Late Triassic) beds of the Calcare di Zorzino (Zorzino Limestone) is described. The holotype and only known specimen represents the first drepanosaurid in which the skull is preserved articulated with the postcranial skeleton. The study of Vallesaurus anatomy confirms previous data about arboreal adaptation in all known drepanosaurids and permits more firm hypotheses about the phylogenetic relationships of the Drepanosauridae to be proposed.